JANUARY 2014 PLACEMENT ADS (The Accounting Review, 2014)
The deadline for free position ads to be included in this section of The Accounting Review is two months prior to the desired publication in the January, March, May, July, September, or November issues. Position ads, which are free with the purchase of a job posting in the AAA Career Center, should provide all relevant information about the available positions and must include contact information or application instructions for interested candidates. For more information on how to purchase a job posting in the Career Center, or for up-to-date, detailed information about the placement listings in this issue, please go to the AAA website at http://aaahq.org and click on “Career Center,” or call our office at 941-921-7747.THE UNIVERSITY OF OKLAHOMA, John T. Steed School of Accounting invites applications for two positions: Assistant, Associate, or Full Professor. The anticipated appointment date is August 15, 2014. Primary needs are for faculty in financial accounting, with a secondary need in managerial accounting. The preferred research focus is empirical archival research. Candidates must possess an appropriate doctorate or be near completion. Candidates must have academic training that indicates the potential for significant high-quality academic research. All qualified individuals may submit application materials to January Nelson, Managerial Associate, Steed School of Accounting, Price College of Business, University of Oklahoma, 307 W. Brooks, AH 200, Norman, OK 73019–4004; Email: jnelson@ou.edu; Phone: (405) 325–4223; Fax: (405) 325–7348. Application materials should include a current vita, copies of publications and working papers, evidence of effective teaching and names and contact information for three references. For questions you may contact the search committee co-chair, Terry Crain. (tcrain@ou.edu).The screening of applications will begin immediately. Applications will be accepted until the positions are filled. The University of Oklahoma is an Equal Opportunity/Affirmative Action Employer. Women and Minorities are encouraged to apply.UNIVERSITY OF MICHIGAN ANN ARBOR, The Ross School of Business has tenure-track positions available in Accounting starting in the 2014 academic year. Candidates with research and teaching interests in all areas of accounting will be considered. Faculty positions at all ranks are available. The application should include a research paper, which may be based on the candidate's dissertation, evidence of teaching experience (if any), and a curriculum vitae that includes three references. To apply, please visit the Stephen M. Ross School of Business at the University of Michigan website: http://www.bus.umich.edu/FacultyRecruiting. The review of applications will begin on November 30, 2013, and we strongly encourage all applications to be completed by that date. Applications will continue to be accepted until January 31, 2014. The University of Michigan offers competitive salary and fringe benefits and is an Equal Opportunity/Affirmative Action Employer.THE INDIANA UNIVERSITY SOUTHEAST, School of Business is currently seeking applicants for a tenure-track appointment beginning in Fall 2014 for a Ph.D. in accounting. Ph.D. in accountancy required. CPA/CMA is desirable. Professional work experience preferred. Applications will be accepted until the position is filled. Starting date is August 1, 2014. Applicants should send vita, three letters of recommendation and transcript to Email: hr@ius.edu; with Attention: Tenure Track in Accounting-Search and Screen Committee. For additional information about the position, call Professor Doug Barney, Chair, Search and Screen Committee, Phone: (812) 941–2532 or Dean Jay White, Phone: (812) 941–2325.THE UNIVERSITY OF PITTSBURGH, Joseph M. Katz Graduate School of Business and College of Business Administration seeks applications for an anticipated tenure-track Assistant Professor position in the accounting area starting Fall 2014 (contingent on budgetary approval and upon authorization to work in the United States). The appointment requires a strong commitment to excellence in scholarly research and teaching. All areas of accounting are appropriate, but preference will be given to empirical (archival) researchers. Applications must be submitted electronically to: http://www.katz.pitt.edu/facultyhiring/accounting-ts.php. Materials submitted must include a letter of interest, vitae/resume, sample research paper(s), evidence of teaching effectiveness, and three letters of reference. The chair of the search committee is Dhinu Srinivasan, email: accfacultysearch@katz.pitt.edu. Application deadline: January 15, 2014. However, we encourage candidates to apply sooner as we will review applications as they are received and continue until the position is filled. The University of Pittsburgh is an Affirmative Action/Equal Opportunity Employer and values equality of opportunity, human dignity and diversity.PASCO-HERNANDO COMMUNITY COLLEGE (PHCC), District Office, New Port Richey Campus is accepting applications for Budget Analyst (Job # 0318). For more information and to apply online visit our website at: http://www.phcc.edu/jobs. Application closing date is October 4, 2013. EOE/ADA Compliance.THE UNIVERSITY OF TEXAS AT ARLINGTON, College of Business is inviting applications for a tenured position as an Associate or Full Professor of Health Care Administration. The successful candidate will serve as Faculty Director for the Master of Science in Health Care Administration program. We seek an individual at the Senior Associate or Full Professor rank and with a research focus on Health Care issues. Candidates will have an earned doctorate, a sustained record of publishing in top journals, and a proven record of teaching excellence. Depending on the candidate's teaching and research interests, their home department may be Accounting, Economics, Finance, Information Systems and Operations Management, Management, or Marketing. Candidates should be actively engaged in research and be a team player willing to build relationships with faculty, students, administration, and the health care community. The University of Texas at Arlington is a researched-focused university with competitive salary, teaching loads, and research support. The appointment is pending budgetary approval and will begin in the Fall 2014. Contact Person: HCAD Faculty Search Committee Email: hcadfacultysearch@uta.edu, Phone: (817) 272–3502. Search Code: BUS09102013HCA. UT Arlington is an Affirmative Action/Equal Opportunity Employer. Women, minorities, veterans, and individuals with disabilities are encouraged to apply. The use of tobacco products is prohibited on UT Arlington properties. A criminal background check will be conducted on finalists.WASHINGTON STATE UNIVERSITY PULLMAN, Department of Accounting, College of Business, invites applications for Assistant Professor in the Department of Accounting. The position will begin August 2014, with duties that include teaching, research, and service. A doctorate in accounting from an AACSB-accredited school is required, although ABD will be considered as long as degree is completed by date of employment. Preference will be given to candidates with a primary teaching interest in financial accounting and evidence of a secondary teaching interest in an additional area of accounting. Candidates must have a record of submissions/publications, or demonstrate the ability to publish, in top tier academic accounting journals and a desire to take an active role working with doctoral students. The following documents are required to be submitted: letter of application, curriculum vitae, an example of scholarly work to be presented to the faculty and Ph.D. students in the event the candidate is selected for an on campus visit, and three letters of recommendation. The application materials must be posted online at http://www.wsujobs.com in order to be considered for the position. Finalists will be required to submit a summary of their student evaluations. Review of applications will begin October 2, 2013, and will continue until the position is filled. Questions regarding the position should be directed to Associate Professor and Department Chair, Sue Gill, Phone: (509) 335–5633, Email: gills@wsu.edu. WSU is an Equal Opportunity/Affirmative Action educator and employer. Members of ethnic minorities, women, Vietnam-era or disabled veterans, persons of disability, and/or persons age 40 or over are encouraged to apply. Accommodations for applicants who qualify under the Americans with Disabilities Act are available upon request. WSU employs only U.S. citizens and lawfully authorized non-U.S. citizens. All new employees must show employment eligibility verification as required by the U.S. Immigration and Naturalization Services.MIDDLE TENNESSEE STATE UNIVERSITY, Department of Accounting, located in Murfreesboro, TN, invites applications for three tenure-track faculty positions at the Assistant/Associate Professor rank (position numbers 110060, 110170, and 110005). Positions begin August 2014. All areas of Accounting will be considered. Earned doctorate in accounting expected (ABD considered if close to completion). CPA or other licenses preferred. Department offers an undergraduate degree in Accounting, a Master of Accountancy, and supports the Accounting concentration in the M.B.A. program. The department earned separate AACSB-accreditation in 2004, and was reaffirmed in 2012. Direct questions to: Dr. G. Robert Smith, Jr., Email: smitty.smith@mtsu.edu, or Dr. Paula Thomas, Email: paula.thomas@mtsu.edu. Reviews of applications begin October 28, 2013, and continue until positions are filled. All applications must be submitted online at MTSU website. To apply go to https://mtsujobs.mtsu.edu. EO/AA Employer. Women and minorities are encouraged to apply.THE UNIVERSITY OF TEXAS AT DALLAS (UTD), Naveen Jindal School of Management invites applications for two faculty positions in Accounting, effective September 2014. Appointment at Assistant, Associate, or Full Professor level will be considered. Appointees must have a Ph.D. in accounting or equivalent (or have an ABD status and expect to have the Ph.D. within a year of hire date) and demonstrate the ability to conduct a nationally recognized research program. Applicants should submit curriculum vitae (education, research, teaching and student evaluations, work experience, a list of publications and presentations) and at least three letters of reference. Visit the URL: http://go.utdallas.edu/pmi130904 for more information. UTD is an Equal Opportunity/Affirmative Action Employer.PLYMOUTH STATE UNIVERSITY, College of Business Administration, an ACBSP-accredited program, invites applications for Faculty Position in Business, Accounting Tenure-Track, benefited position in Accounting beginning in August 15, 2014. We seek a talented individual at the Instructor or Assistant Professor level with a record of teaching excellence, experience teaching diverse learners, experience integrating technology with instruction, a willingness to teach traditional, blended and online graduate and undergraduate classes, and demonstrated or strong potential for future scholarship. Apply online at: https://jobs.usnh.edu/applicant/Central?quickFind=53665 to receive for this School of Management seeks applicants for a tenure-track position at the Assistant Professor level in the Department of Accounting starting Fall 2014. Applicants must demonstrate an ability to high-quality accounting research and the potential for excellence in teaching at the undergraduate and graduate We seek individuals with an for and Applicants should provide a curriculum vitae, of work and three letters of reference. Applications received 1, will be considered. candidates should apply online at College is an Equal Opportunity UNIVERSITY invites applications for an Assistant/Associate Professor in the Department of Accounting and to begin August 2014. primary need is for a faculty who teach accounting information and accounting faculty are expected to academic with as as to to and university The School of Business is by Candidates should have a Ph.D. in Accounting from an AACSB-accredited or be the of a program. Candidates must demonstrate the potential for teaching excellence and research Robert located in the of is to high-quality instruction, engaged with a and to our students. To apply include a letter of application, curriculum vita, teaching evaluations, evidence of copies of and a list of three academic and/or references. Visit for additional information. Apply to: Email: Department of Accounting and we that our commitment to a is and and as as and UNIVERSITY, School of Business, seeks at the Assistant Professor level to to the of research. candidates should have a Ph.D. or equivalent by September 1, 2014, and have the potential for excellence in research, teaching, and in all areas are encouraged to apply for positions starting in or September 2014. we Assistant candidates at ranks may be considered if they qualify and our and teaching are for campus will begin in Fall 2013. University students, and is of the three research in over students and faculty, the School is of the and in the and Ph.D. in and at in the and The School is in an by of and are ranks the M.B.A. in the top in the The ranks M.B.A. in the top in the and the M.B.A. in the top in the U.S. The U.S. the M.B.A. at in the which is the in the the in the United is an with a concentration of and other as as is close to New and are the of U.S. has a significant of financial and other for research and with and employment for and and to campus and be at: may a of the by Campus at: Phone: information is available from the and department at Application materials should be received by November 30, 2013. Applications should include a curriculum vitae, a of research interests, an example of scholarly evidence of excellence in teaching, and the names and contact information of three references. submit electronically to: and send of materials to: Department of Accounting, School of Business, University is an Equal Opportunity/Affirmative Action Employer and invites applications from and UNIVERSITY OF AT School of Business a tenure-track position in Accounting at the Assistant Professor level beginning August 2014 position applicants should be to excellence in teaching, and research. The candidate will have a primary interest in teaching at the undergraduate and graduate A Ph.D. in Accounting is preferred considered if degree is completed by August 1, but will with a in The School of Business is faculty serve graduate students in the in Accounting, and in Science and Information Systems To apply, please online application at: A letter of application to the of the Search Committee, a teaching evaluations, and contact information for three current must be to the online application in or For questions regarding the online application contact at Phone: or Email: will be given to applications received by November 2013, but applications will be accepted until the position is filled. actively a diverse and working and and is an Equal Opportunity UNIVERSITY, Graduate School of Management invites applications for tenure-track positions in our Accounting Applicants at all ranks with research and teaching interests in financial or managerial accounting will be considered. Applicants must have a Ph.D. in Accounting or or be close to completion. of the include research in of teaching and in accounting at the M.B.A. and Ph.D. of doctoral and to the University is an university and a to of students, and an of and to the of teaching, and in includes the on the of and as as the new campus to be on in the of New To be considered for this position, send vita, copies of research papers, names and contact information of three and other to: candidates and must provide letters of recommendation from their references. Application is November 30, 2013. 2014. and have and continue to be a of our University is a recognized and STATE UNIVERSITY, College of Business invites applicants for of The Chair, by the and Jr., and the of on The is expected to demonstrate excellence as a and include two in the and in the at undergraduate and/or graduate to publications in scholarly journals is and and as a for the accounting are an earned in Accounting and record of scholarly teaching, and in the of The located in TN, has from at the undergraduate and graduate The College seeks the on a tenure-track or to take accounting to the level of effective teaching, scholarly and research, and The individual selected for the should an earned doctorate in accounting and a record of scholarly teaching, and in accounting. All areas of in accounting will be considered. will teach undergraduate and/or graduate on a will research to publication in journals, will in the of the and teaching for Professor who research and publication is We seek a candidate with a commitment in working with students, faculty, and from diverse in Accounting or equivalent is required (ABD be considered at the Assistant with current or accounting experience preferred. Applicants for must have evidence of teaching as as a demonstrated record of research and publication required. Apply URL: The appointment will begin August 2014. The salary is competitive with AACSB-accredited The deadline for applications is January 31, 2014. Candidates are to an online application with of John an application at the following website: For additional contact Dr. College of Business at Email: University with and is Affirmative Action OF invites applications for a tenure-track faculty position, for Fall 2014. Preference will be given to applicants who show of significant teaching and research within an of on the of and The candidate must scholarly research publications in high-quality accounting Candidates for an Assistant Professor position must or be near of an earned doctorate in accounting (or in with a in show for effective teaching and with students, and demonstrate an ability to high-quality research. Candidates for an Associate Professor position must a doctorate in accounting and have an record of high-quality teaching and research, publications in accounting Professional in accounting or is desirable. of The is a research university in the The university is the for on for students and a letter of interest, current vita, teaching and research a sample of the research, and a list of three electronically at: for the Assistant Professor position or for the Associate Professor UNIVERSITY OF is seeking tenure-track accounting faculty positions at the rank of Assistant, Associate, or Full Professor to begin Fall 2014. candidates will be expected to conduct high-quality research in academic journals, in and academic and research in their areas of will be expected to teach appropriate at the or Ph.D. the of Ph.D. students, and in and Ph.D. (or in Accounting expected by August 2014. Applicants at the rank of Instructor or Assistant must show of excellence in research and teaching. Applicants at ranks should possess an record of research teaching and in and doctoral evidence of to the the or the in and university successful in undergraduate and/or graduate curriculum demonstrated ability to research, teaching, and/or to the and excellence of the are tenure-track positions with an anticipated date of August 2014. primary academic appointment will be at the with the of work at the will be with and To apply, please visit at: The University of is an EO/AA OF College of and seeks a faculty, tenure-track or Full Professor or position. September 2014. October 2013. Application review October 15, 2013. until filled. For job please visit To submit a letter on an accounting in a university and demonstrated in teaching and a and three letters of reference. for a tenure-track position should include evidence of successful in the materials to: with the Americans with Disabilities if selected for the and are please call Members of are encouraged to apply. Equal Opportunity a with a commitment to excellence in undergraduate invites applications for a tenure-track appointment in the and Business Department beginning August 2014. Candidates should be to teach accounting and and the Ph.D. or ABD at preferred in or accounting. The candidate must be qualified graduate to teach and accounting Candidates must have a strong commitment to teaching. a in is located in and has an of students. letter of application, curriculum vita, undergraduate and graduate of teaching and three letters of recommendation to: Accounting Search Committee, Department of Economics, Review of applications will begin on 1, 2013. We will be at the in in more about at: UNIVERSITY, School of Business invites applications for a position to budgetary in Accounting, with preference for level in Managerial Accounting. Candidates must have a or be near completion. The successful candidate will strong potential for and high-quality scholarly research to as as for teaching and an commitment to academic and excellence, in of the and The accounting area of who in top journals and seek to For more information about our faculty The effective date of the appointment will be 1, 2014, but is a current three letters of a of research interests, a of teaching interests and experience teaching if and at least working or electronically to: Dr. Associate is to employment and in the The academic at are by a posted at: is an to candidates of all However, in with Immigration will be given to citizens and STATE UNIVERSITY OF Business and New invites applications for a tenure-track at the Professor level in the department of Accounting and Information All ranks will be considered. A strong commitment to excellence in high-quality research and in teaching at the undergraduate and graduate A Ph.D. degree from an AACSB-accredited school in the of accounting or a is required. However, candidates at the Assistant level who are close to of their degree will be considered. Candidates at the Associate or Professor level must have an research record with the level of and salary are competitive with research Application The review of applications will begin and applications will be accepted until the position is filled. the following documents with application vita, and job Finalists will be to three letters of and other materials as by the Search Committee. Apply electronically by application to: Professor Search Committee Email: will be University is an Affirmative Action/Equal Opportunity Employer. Women, of and persons with disabilities are encouraged to apply.THE UNIVERSITY OF Department of Accounting, Economics, and is seeking an to our tenure-track appointment in Candidates must a Ph.D. in Accounting or from an AACSB-accredited school or be ABD their to with accounting is a We will candidates with research and teaching interests in all but our needs are in financial accounting. competitive and candidates should contact Chair, Department of Accounting, Economics, and Finance, The University of in Email: include a and at least three with letter of is an Affirmative Action/Equal Opportunity We encourage applications from and UNIVERSITY, School of Business is seeking to a position in Accounting and of will be Accounting or The appointment will be effective 1, 2014, or as as and benefits are competitive and to The preferred candidate will a Ph.D. in Accounting, or a record of high-quality research, publications in top journals in accounting or The candidate the ability to in evidence of high-quality teaching at graduate and undergraduate and eligibility for appointment to the Faculty of Graduate willingness and ability to to the doctoral in accounting and All University positions are to budgetary The deadline for completed applications is January 31, 2014. Applicants should send an application, application curriculum vitae, of research papers, names and of three and information regarding teaching to: Dr. Professor of Accounting, Dr. Professor of Finance, Assistant, Email: University is an Affirmative Action Employer. The Affirmative Action be on website at: or a be by the Affirmative Action office at All qualified candidates are encouraged to citizens and will be given UNIVERSITY OF The School of Business invites applications for a tenure-track Assistant or Associate Professor of Accounting, on The required and preferred for rank may be at the following The successful candidate will be expected to teach undergraduate in accounting and in or two of the following accounting and accounting information teaching in the is job include an active research to publication of working with students in a with in the and in include teaching online and teaching in our on the The position August 2014. The School offers an a Professional an in an in and an undergraduate program, and is by Visit our home at: candidates should submit a letter of interest, current or curriculum vitae, of teaching and three references. Email: to include and in of applications November 15, and until OF Department of Accountancy, invites applicants for the and Professor of Accountancy, an The department seeks applicants with a record and of research, a record of and interest in effective teaching, and the to actively in the research and teaching The University of an research undergraduate students and graduate students. within the College of Business, the Department employs tenure-track faculty and faculty, and two an undergraduate and an in program. For more please visit submit a vita, and evidence of teaching to: Equal Opportunity the University of applicants who the COLLEGE in seeks a to accounting The successful candidate will teach as as other based on individual to teaching, the successful candidate will be expected to be active in scholarly research, to the program, and to the an that with information to College is currently AACSB-accreditation and is seeking a candidate who our new will be to teaching in a academic and will and of that The successful candidate must possess of the a Ph.D. in a graduate degree in or an appropriate of graduate in and accounting. Preference will be given to candidates with the following a Ph.D. in accounting with an in ability to teach graduate and undergraduate and other area accounting, financial accounting, or in relevant and demonstrated ability to work with diverse student For posting and to apply, use our online application at: